Environmental and socioeconomic health inequalities: a review and an example of the industrial Ostrava region - Šlachtová, Hana; Jiřík, Vítězslav; Tomášek, Ivan; Tomášková, Hana (Central European Journal of Public Health, 2016)
BACKGROUND: According to the World Health Organization (WHO) more than 2 million premature deaths and 7 million of total deaths each year can be attributed to the effects of air pollution. The contribution of air pollution to the health status of population is estimated to be about 20%. Health is largely determined by factors outside the reach of healthcare sector, including low income, unemployment, poor environment, poor education, and substandard housing. AIM: The aim of the paper was to review a current knowledge of relationships among air pollution, socioeconomic health inequalities, socio-spatial differentiation, and environmental inequity. The relationships were demonstrated on an example of the Ostrava region. Also basic approaches to health valuation were reviewed. RESULTS: Social differences are reasons both for health inequalities and spatial patterns of unprivileged area housing. In urban environments with poor air quality there is also a large concentration of low income residents. Less affluent population groups are more often affected by inadequate housing conditions including second-hand smoking and higher environmental burden in their residential neighbourhoods. Environmental injustice is highly correlated with other factors that link poverty with poor health, including inadequate access to medical and preventive care, lack of availability of healthful food, lack of safe play spaces for children, absence of good jobs, crime, and violence. CONCLUSIONS: The theoretical background and also results of the studies brought evidence that population health is affected by both socioeconomic and environmental inequalities. Air pollution is unevenly distributed in Ostrava and is related to distribution of socially disadvantaged environment and social exclusion as well.
Keywords: disparity zdravotního stavu; látky znečišťující vzduch; vystavení vlivu životního prostředí; lidé; Environmental Exposure; sociální determinanty zdraví; Czech Republic; Air Pollutants; Air Pollution; Health Status Disparities; průmysl; Industry; Humans; znečištění ovzduší; Česká republika; Social Determinants of Health